2020
DOI: 10.1212/nxi.0000000000000753
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 infection in a patient with multiple sclerosis treated with fingolimod

Abstract: In December 2019, a novel coronavirus causing an infectious respiratory disease was identified, which since then has developed into a pandemic with higher rates of mortality in older individuals and those with underlying medical conditions. 1 Multiple sclerosis (MS) is an immune-mediated neurologic disease which requires long-term treatment with immunotherapies that have been shown to increase the risk of infections. 2 As a result, there is significant anxiety among patients and neurologists during the pandem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
67
0
5

Year Published

2020
2020
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(74 citation statements)
references
References 7 publications
(6 reference statements)
2
67
0
5
Order By: Relevance
“…In such patients, the administration of IVIG may improve outcomes whereas hydroxychloroquine could worsen the myasthenic crisis [157]. A case report study of a relapsing-remitting multiple sclerosis (MS) patient with SARS-CoV2 infection reported a worsening of neurological symptoms at initial presentation [158]. While the current consensus is to continue disease-modifying treatments, SARS-CoV-2 infected MS patients may benefit from.…”
Section: Challenges For the Clinical Management Of Covid-19mentioning
confidence: 99%
“…In such patients, the administration of IVIG may improve outcomes whereas hydroxychloroquine could worsen the myasthenic crisis [157]. A case report study of a relapsing-remitting multiple sclerosis (MS) patient with SARS-CoV2 infection reported a worsening of neurological symptoms at initial presentation [158]. While the current consensus is to continue disease-modifying treatments, SARS-CoV-2 infected MS patients may benefit from.…”
Section: Challenges For the Clinical Management Of Covid-19mentioning
confidence: 99%
“…Foerch et al reported that multiple sclerosis patient with severe COVID-19 infection was being treated with Fingolimod. The patient improved rapidly right after appropriate therapy 76 . Integrin complexes have multiple implications in immune cell migration and viral infection.…”
Section: Discussionmentioning
confidence: 89%
“…Barzegar M. et al described a case report of COVID-19 in a MS patient treated with fingolimod. She had a favorable outcome after discontinuation on fingolimod and was discharged after resolution of symptoms [ 13 ]. Another case report by Novi G. et al described SARS-CoV-2 infection in an MS patient on Ocrelizumab and explored a possible protective role of immunosuppressive therapy for COVID-19 infection.…”
Section: Discussionmentioning
confidence: 99%